2013
DOI: 10.1017/s1478951513000229
|View full text |Cite
|
Sign up to set email alerts
|

Understanding communication among health care professionals regarding death and dying in pediatrics

Abstract: Health care professionals who felt comfortable discussing options for end of life care with colleagues also felt more comfortable: initiating a discussion regarding a child's impending death with his/her family (r = 0.42), discussing options for terminal care with a family (r = 0.58), discussing death with families from a variety of ethnic/cultural backgrounds (r = 0.51), guiding parents in developmentally age-appropriate discussions of death with their children (r = 0.43), identifying and seeking advice from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 10 publications
1
27
0
1
Order By: Relevance
“…This finding was consistent with previous indications 15 that communication was an essential element of quality palliative care. The nurses also thought that including the child in treatment decisions was essential.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This finding was consistent with previous indications 15 that communication was an essential element of quality palliative care. The nurses also thought that including the child in treatment decisions was essential.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the results of a study 14 in which participants viewed families' caring for children with palliative care needs as a major undertaking. In addition, Harrison et al 15 reported that long-term adverse effects when families could not cope with the loss of the families' once-normal children often led to destruction of the family. The nurses, who were also parents, stated they themselves would not give up on their own child until the very end.…”
Section: Discussionmentioning
confidence: 99%
“…, Harrison et al . ). Most nurses expressed anxiety about making errors in handling medicines because the dosages and strengths were different from what they were used to.…”
Section: Discussionmentioning
confidence: 97%
“…This perception is ambiguous: despite recognizing that early referrals are recommended, they seem to view palliative care as hospice care. 4,6,7 In addition, they recognized several barriers to delivering palliative care, while simultaneously understanding that a palliative care team could offer additional benefits to patients/families. 4,[6][7][8] To our knowledge, this study is the first nationwide investigation of perceptions of PPC among physicians caring for pediatric patients in tertiary hospitals in Korea.…”
Section: Introductionmentioning
confidence: 99%